A high-coloring masterbatch and preparation method thereof
By modifying the carrier resin, combined with vermiculite and hydrotalcite modified polyethylene/EVA resin, the problems of uneven dispersion and poor coloring of masterbatches during the production process are solved, and the high coloring power and flame retardant performance are improved.
Patent Information
- Application Number
- CN202411447624.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
During the production process, the masterbatches are unevenly dispersed due to raw materials, formulas and processing technology, and the colorant is poorly diffused, and color points with poor surface dispersion appear. The product has defects such as surface color and gloss defects, dark surface color and other defects.
By modifying the carrier resin, the modified polyethylene/EVA resin with vermiculite and hydrotalcite are used as the carrier, and combined with colorant, dispersant, lubricant and antioxidant, it is extruded and granulated through a twin-screw extruder to obtain a color masterbatch with high coloring power.
The high color force and color dispersion of the masterbatch are achieved, which eliminates the color points of poor surface dispersion, improves the color uniformity and gloss of the product, and improves the flame retardant performance of the masterbatch.
Smart Images

Figure BDA0005088143150000081 
Figure BDA0005088143150000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a masterbatch with high tinting power and a preparation method thereof. Background Art
[0002] Masterbatch is a kind of polymer composite coloring material made by using resin as carrier, adding high proportion of pigment, dispersant and functional additives, through high-speed mixing, melt mixing and extrusion, cooling and pelletizing. Masterbatch is an important material widely used in various industries and plays an indispensable role in modern industry.
[0003] Pigments are the effective ingredients for coloring masterbatches. White masterbatches usually use titanium dioxide as pigments, while black masterbatches usually use carbon black as pigments. Color masterbatches are rich in color and use a wide variety of pigments, such as azo pigments, phthalocyanine pigments, and metal oxide pigments. In the production process of masterbatches, their quality is closely related to the dispersibility of the pigments.
[0004] In the actual production process, due to reasons such as raw materials, formula, and processing technology, masterbatch mixing and dispersion will be uneven, colorant diffusion will be poor, there will be serious poorly dispersed color spots on the surface of the masterbatch, and the finished products will have defects such as surface color and gloss defects, and surface dark color. Summary of the invention
[0005] The object of the present invention is to provide a masterbatch with high tinting power and a preparation method thereof, and to improve the tinting power and coloring dispersibility of the masterbatch by modifying the carrier resin.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The present invention provides a masterbatch with high tinting power, which comprises the following raw materials in parts by mass:
[0008] 40-50 parts of carrier resin, 5-20 parts of colorant, 8-16 parts of dispersant, 4-5 parts of lubricant and 1-3 parts of antioxidant;
[0009] The carrier resin is polyethylene / EVA resin modified by vermiculite and hydrotalcite.
[0010] Vermiculite is a natural layered mineral material with a confined structure consisting of two layers of silicon-oxygen tetrahedrons and one layer of aluminum-oxygen octahedrons, which carries a negative charge. The interlayers between the structural layers are water molecules and exchangeable cation layers. The interlayers of vermiculite are exchangeable, so they show good adsorption properties.
[0011] Hydrotalcite is a type of layered two-dimensional material with positively charged metal hydroxide layers and charge-balancing intercalated anions, and has good anion exchange properties.
[0012] Furthermore, the preparation steps of the carrier resin are as follows:
[0013] S1, grinding vermiculite to a particle size of 100-150 μm, adding it to a 1 mol / L sodium chloride solution, heating it to 60°C, stirring it at a constant temperature for 24 hours, centrifuging it, repeatedly washing it with deionized water for 5 times, and drying it at 60°C to obtain sodium vermiculite;
[0014] S2, adding sodium vermiculite and hexadecyltrimethylammonium bromide in a mass ratio of 5:1 into deionized water, stirring at 65° C. for 24 h, and then centrifugally drying to obtain modified vermiculite;
[0015] S3, adding hydrotalcite and sodium dodecyl sulfate into deionized water, ultrasonicating for 30 minutes, adding sodium hydroxide to adjust the pH to 9.5, stirring at 60°C in a water bath for 3 hours, centrifuging and repeatedly washing with deionized water, adjusting the pH to 7.0-8.0, soaking in anhydrous ethanol for 30 minutes, filtering, and drying at 80°C to obtain modified hydrotalcite;
[0016] S4. Mix the modified hydrotalcite and EVA resin to obtain a mixture A, and mix the modified vermiculite and polyethylene resin to obtain a mixture B. Heat the mixture A to 90-100° C., stir for 1-2 hours, add the mixture B, stir and mix, then heat to 160-180° C., stir for 1-2 hours, and place in an extruder for extrusion and granulation to obtain a carrier resin.
[0017] Since vinyl acetate monomer is introduced into EVA resin, its crystallinity is significantly reduced, thereby improving flexibility, impact resistance and heat sealing. EVA resin has good filler tolerance and cross-linking. At the same time, EVA resin has a significantly lower melting point than polyethylene resin, and there is a difference in fluidity between the two at the same temperature. Melting the EVA resin first and then adding the polyethylene resin to melt can make the EVA resin with higher fluidity and the polyethylene resin fully contact and mix.
[0018] After being modified with sodium dodecyl sulfate, long-chain alkyl and sulfonic acid groups are introduced into hydrotalcite, making it more compatible with EVA resin. After being modified with hexadecyltrimethylammonium bromide, vermiculite has enhanced hydrophobicity. Polyethylene resin is a non-polar polymer, and the modified vermiculite has good compatibility with polyethylene resin.
[0019] Furthermore, the ratio of vermiculite to sodium chloride solution in S1 is 1 g / 4 mL, the vermiculite is Xinjiang Yuli vermiculite, and the cation exchange capacity is 98.6 mmol / 100 g.
[0020] Vermiculite has good expansion properties. The burning of resin causes the vermiculite to expand, which can increase the coverage area of the carbon layer and improve the flame retardant performance.
[0021] Furthermore, the mass ratio of sodium vermiculite to deionized water in S2 is 1:10.
[0022] Furthermore, in the S3, the mass ratio of hydrotalcite to sodium dodecyl sulfate is 20:1, the mass ratio of hydrotalcite to deionized water is 3:20, the particle size of the hydrotalcite is 5-10 μm; and the hydrotalcite is hydrated magnesium aluminate carbonate.
[0023] When hydrotalcite is heated, it releases carbon dioxide and absorbs a large amount of heat, which can reduce the temperature of the combustion system. The magnesium aluminum oxide generated by thermal decomposition will form a protective film, which can block the intrusion of oxygen and have a flame retardant effect.
[0024] Furthermore, the mass ratio of the modified hydrotalcite to the EVA resin in S4 is 0.6-1:4.
[0025] Furthermore, the mass ratio of the modified vermiculite to the polyethylene resin in S4 is 1-2:9.
[0026] Furthermore, the mass ratio of mixture A to mixture B in S4 is 1:3.
[0027] The present invention also provides a method for preparing a masterbatch with high tinting power, and the preparation steps of the masterbatch are as follows:
[0028] The raw materials are weighed in proportion, the carrier resin, the colorant, the dispersant, the lubricant and the antioxidant are mixed, and then put into a twin-screw extruder for extrusion granulation to obtain a masterbatch.
[0029] Further, the colorant is at least one of an organic pigment and an inorganic pigment;
[0030] The organic pigments include phthalocyanine pigments and azo pigments;
[0031] The inorganic pigment is titanium dioxide;
[0032] The dispersant is polyethylene wax; the lubricant is calcium stearate; and the antioxidant is antioxidant 1010.
[0033] Beneficial effects of the present invention:
[0034] Vermiculite is modified with hexadecyltrimethylammonium bromide, and hydrotalcite is modified with sodium dodecylsulfonate. The obtained modified vermiculite and modified hydrotalcite have good compatibility with resin. The modified hydrotalcite and EVA resin are mixed and melted, and then the modified vermiculite and polyethylene resin are added. Since the layers of vermiculite and hydrotalcite are charged, the different components can be fully and evenly mixed and dispersed through the attraction of positive and negative charges. The physical properties of the surfaces of vermiculite and hydrotalcite, such as the porous structure and large specific surface area, can promote the adsorption of dye molecules, so that the masterbatch prepared by mixing the carrier resin and the colorant has high tinting power and uniform coloring. At the same time, the expansion performance of the vermiculite and the release of carbon dioxide by thermal decomposition of the hydrotalcite can improve the flame retardant performance of the masterbatch. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Preparation of carrier resin:
[0038] S1, grinding vermiculite to a particle size of 100-150 μm, adding it to a 1 mol / L sodium chloride solution, the ratio of vermiculite to sodium chloride solution is 1 g / 4 mL, heating to 60° C., stirring at constant temperature for 24 h, centrifuging, repeatedly washing with deionized water 5 times, and drying at 60° C. to obtain sodium vermiculite;
[0039] S2, adding sodium vermiculite and hexadecyltrimethylammonium bromide into deionized water in a mass ratio of 5:1, the mass ratio of sodium vermiculite to deionized water is 1:10, stirring at a constant temperature of 65°C for 24 hours, and then centrifugally drying to obtain modified vermiculite;
[0040] S3, adding hydrotalcite (hydrated magnesium aluminate carbonate with a particle size of 5-10 μm) and sodium dodecyl sulfate into deionized water in a mass ratio of 20:1, the mass ratio of hydrotalcite to deionized water is 3:20, ultrasonicating for 30 min, adding sodium hydroxide to adjust the pH to 9.5, stirring in a water bath at 60°C for 3 h, centrifuging and repeatedly washing with deionized water, adjusting the pH to 7.0-8.0, soaking in anhydrous ethanol for 30 min, filtering, and drying at 80°C to obtain modified hydrotalcite;
[0041] S4. Mix the modified hydrotalcite and EVA resin to obtain a mixture A, the mass ratio of the modified hydrotalcite and the EVA resin is 0.6:4. Mix the modified vermiculite and the polyethylene resin to obtain a mixture B, the mass ratio of the modified vermiculite and the polyethylene resin is 1:9. Heat the mixture A to 90-100°C, stir for 1-2h, add the mixture B, stir and mix, then heat to 160-180°C, the mass ratio of the mixture A to the mixture B is 1:3, stir for 1-2h, place in an extruder for extrusion and granulation to obtain a carrier resin.
[0042] Example 2
[0043] The difference from Example 1 is that the mass ratio of modified hydrotalcite to EVA resin in mixture A is adjusted to 0.8:4, and the other steps and conditions are the same as Example 1.
[0044] Example 3
[0045] The difference from Example 1 is that the mass ratio of modified hydrotalcite to EVA resin in mixture A is adjusted to 1:4, and the other steps and conditions are the same as Example 1.
[0046] Example 4
[0047] The difference from Example 1 is that the mass ratio of modified vermiculite to polyethylene resin in mixture B is adjusted to 1.5:9, and the other steps and conditions are the same as Example 1.
[0048] Example 5
[0049] The difference from Example 1 is that the mass ratio of modified vermiculite to polyethylene resin in mixture B is adjusted to 2:9, and the other steps and conditions are the same as Example 1.
[0050] Example 6
[0051] This embodiment provides a masterbatch with high tinting power, and its raw materials include, by weight:
[0052] 40 parts of the carrier resin prepared in Example 1, 5 parts of fast red, 8 parts of polyethylene wax, 4 parts of calcium stearate and 10101 parts of antioxidant.
[0053] The preparation steps of the above masterbatch are as follows:
[0054] The raw materials were weighed according to the above proportions, and the carrier resin, light-fast red, polyethylene wax, calcium stearate and antioxidant 1010 were put into a mixing mixer at 300 r / min and stirred for 40 minutes, and then put into a twin-screw extruder for extrusion granulation. The temperature of the extruder was set at 170-200°C to obtain masterbatch.
[0055] Example 7
[0056] The difference from Example 6 is that the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Example 2, and the other steps and conditions are the same as Example 6.
[0057] Example 8
[0058] The difference from Example 6 is that the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Example 3, and the other steps and conditions are the same as Example 6.
[0059] Example 9
[0060] The difference from Example 6 is that the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Example 4, and the other steps and conditions are the same as Example 6.
[0061] Example 10
[0062] The difference from Example 6 is that the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Example 5, and the other steps and conditions are the same as Example 6.
[0063] Embodiment 11
[0064] The difference from Example 6 is that the raw material ratio is adjusted to: 45 parts of the carrier resin prepared in Example 1, 10 parts of light-fast red, 12 parts of polyethylene wax, 4.5 parts of calcium stearate and 10102 parts of antioxidant, and the other steps and conditions are the same as Example 6.
[0065] Example 12
[0066] The difference from Example 6 is that the raw material ratio is adjusted to: 50 parts of the carrier resin prepared in Example 1, 20 parts of light-fast red, 16 parts of polyethylene wax, 5 parts of calcium stearate and 10103 parts of antioxidant, and the other steps and conditions are the same as Example 6.
[0067] Comparative Example 1
[0068] Compared with Example 1, the carrier resin of this comparative example is not modified by adding hydrotalcite. The specific steps of preparing the carrier resin are as follows:
[0069] S1, grinding vermiculite to a particle size of 100-150 μm, adding it to a 1 mol / L sodium chloride solution, the ratio of vermiculite to sodium chloride solution is 1 g / 4 mL, heating to 60° C., stirring at constant temperature for 24 h, centrifuging, repeatedly washing with deionized water 5 times, and drying at 60° C. to obtain sodium vermiculite;
[0070] S2, adding sodium vermiculite and hexadecyltrimethylammonium bromide into deionized water in a mass ratio of 5:1, the mass ratio of sodium vermiculite to deionized water is 1:10, stirring at a constant temperature of 65°C for 24 hours, and then centrifugally drying to obtain modified vermiculite;
[0071] S3. Take EVA resin as mixed material A, and mix modified vermiculite and polyethylene resin to obtain mixed material B, the mass ratio of modified vermiculite to polyethylene resin is 1:9, heat mixed material A to 90-100°C, stir for 1-2h, add mixed material B, stir and mix, then heat to 160-180°C, the mass ratio of mixed material A to mixed material B is 1:3, stir for 1-2h, place in an extruder for extrusion and granulation to obtain a carrier resin.
[0072] Comparative Example 2
[0073] Compared with Example 1, no vermiculite modification is added to the carrier resin of this comparative example. The specific steps for preparing the carrier resin are as follows:
[0074] S1. Add hydrotalcite (hydrated magnesium aluminate carbonate with a particle size of 5-10 μm) and sodium dodecyl sulfate into deionized water in a mass ratio of 20:1, and the mass ratio of hydrotalcite to deionized water is 3:20. Ultrasonicate for 30 min, add sodium hydroxide to adjust the pH to 9.5, stir in a water bath at 60°C for 3 h, centrifuge and repeatedly wash with deionized water, adjust the pH to 7.0-8.0, soak in anhydrous ethanol for 30 min, filter, and dry at 80°C to obtain modified hydrotalcite.
[0075] S2. Mix the modified hydrotalcite and EVA resin to obtain a mixture A, wherein the mass ratio of the modified hydrotalcite and the EVA resin is 0.6:4, and the polyethylene resin is used as the mixture B. Heat the mixture A to 90-100°C, stir for 1-2 hours, add the mixture B, stir and mix, then heat to 160-180°C, wherein the mass ratio of the mixture A to the mixture B is 1:3, stir for 1-2 hours, place in an extruder for extrusion and granulation, and obtain a carrier resin.
[0076] Comparative Example 3
[0077] Compared with Example 1, the carrier resin of this comparative example is not modified by adding vermiculite and hydrotalcite. The specific steps of preparing the carrier resin are as follows:
[0078] Heat the EVA resin to 90-100°C, stir for 1-2 hours, add the polyethylene resin, stir and mix, then heat to 160-180°C, the mass ratio of the EVA resin to the polyethylene resin is 1:3, stir for 1-2 hours, place in an extruder for extrusion and granulation to obtain a carrier resin.
[0079] Comparative Example 4
[0080] Compared with Example 6, in this comparative example, the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Comparative Example 1, and the other steps and conditions are the same as those in Example 6.
[0081] Comparative Example 5
[0082] Compared with Example 6, in this comparative example, the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Comparative Example 2, and the other steps and conditions are the same as in Example 6.
[0083] Comparative Example 6
[0084] Compared with Example 6, in this comparative example, the carrier resin prepared in Example 1 is replaced by the carrier resin prepared in Comparative Example 3, and the other steps and conditions are the same as in Example 6.
[0085] The masterbatches prepared in Examples 6 to 12 and Comparative Examples 4 to 6 were tested for performance, and the results are shown in Table 1.
[0086] The color strength and dispersion test were tested according to the reference standard "QB1648-1992 Polyethylene Color Masterbatch".
[0087] The flame retardant grade test is tested with reference to the standard "GBT2408-2021 Horizontal and vertical methods for determination of combustion performance of plastics".
[0088] Table 1
[0089]
[0090]
[0091] As can be seen from Table 1, the coloring performance and flame retardant performance of the masterbatch of the embodiment are significantly improved compared with the comparative example. In Examples 6-10, by adjusting the content of hydrotalcite and vermiculite, a masterbatch with less usage and optimal performance can be obtained. In Comparative Examples 4 and 5, hydrotalcite or vermiculite is added alone. Since there is no mutual attraction between positive and negative charge materials, the dispersibility will be reduced, and the coloring performance and flame retardant performance of the masterbatch will be reduced.
[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A masterbatch with high tinting power, characterized in that: The following raw materials are included by mass: 40-50 parts of carrier resin, 5-20 parts of colorant, 8-16 parts of dispersant, 4-5 parts of lubricant and 1-3 parts of antioxidant; The carrier resin is a polyethylene / EVA resin modified by vermiculite and hydrotalcite; The preparation steps of the carrier resin are as follows: S1, grinding vermiculite to a particle size of 100-150 μm, adding it to a 1 mol / L sodium chloride solution, heating it to 60°C, stirring it at a constant temperature for 24 hours, centrifuging it, repeatedly washing it with deionized water for 5 times, and drying it at 60°C to obtain sodium vermiculite; S2, adding sodium vermiculite and hexadecyltrimethylammonium bromide in a mass ratio of 5:1 into deionized water, stirring at 65° C. for 24 h, and then centrifugally drying to obtain modified vermiculite; S3, adding hydrotalcite and sodium dodecyl sulfate into deionized water, ultrasonicating for 30 minutes, adding sodium hydroxide to adjust the pH to 9.5, stirring at 60°C in a water bath for 3 hours, centrifuging and repeatedly washing with deionized water, adjusting the pH to 7.0-8.0, soaking in anhydrous ethanol for 30 minutes, filtering, and drying at 80°C to obtain modified hydrotalcite; S4. Mix the modified hydrotalcite and EVA resin to obtain a mixture A, and mix the modified vermiculite and polyethylene resin to obtain a mixture B. Heat the mixture A to 90-100° C., stir for 1-2 hours, add the mixture B, stir and mix, then heat to 160-180° C., stir for 1-2 hours, and place in an extruder for extrusion and granulation to obtain a carrier resin.
2. The high coloring power masterbatch according to claim 1, characterized in that: The ratio of vermiculite to sodium chloride solution in S1 is 1 g / 4 mL, the vermiculite is Xinjiang Yuli vermiculite, and the cation exchange capacity is 98.6 mmol / 100 g.
3. The high coloring power masterbatch according to claim 1, characterized in that: The mass ratio of sodium vermiculite to deionized water in S2 is 1:
10.
4. The high coloring power masterbatch according to claim 1, characterized in that: The mass ratio of hydrotalcite to sodium dodecyl sulfate in S3 is 20:1, the mass ratio of hydrotalcite to deionized water is 3:20, the particle size of hydrotalcite is 5-10 μm; and the hydrotalcite is hydrated magnesium aluminate carbonate.
5. The high coloring power masterbatch according to claim 1, characterized in that: The mass ratio of the modified hydrotalcite to the EVA resin in S4 is 0.6-1:
4.
6. The high coloring power masterbatch according to claim 1, characterized in that: The mass ratio of modified vermiculite to polyethylene resin in S4 is 1-2:
9.
7. The high coloring power masterbatch according to claim 1, characterized in that: The mass ratio of the mixture A to the mixture B in S4 is 1:
3.
8. A method for preparing a masterbatch with high tinting power as claimed in any one of claims 1 to 7, characterized in that: The preparation steps of the masterbatch are as follows: The raw materials are weighed in proportion, the carrier resin, the colorant, the dispersant, the lubricant and the antioxidant are mixed, and then put into a twin-screw extruder for extrusion granulation to obtain a masterbatch.
9. The method for preparing a masterbatch with high tinting power according to claim 8, characterized in that: The colorant is at least one of an organic pigment and an inorganic pigment; The organic pigments include phthalocyanine pigments and azo pigments; The inorganic pigment is titanium dioxide; The dispersant is polyethylene wax; the lubricant is calcium stearate; and the antioxidant is antioxidant 1010.
Citation Information
Patent Citations
Special anti-ageing dimming red masterbatch for solanaceous fruit vegetable greenhouse film and preparation method of anti-ageing dimming red masterbatch
CN104558798A
Special anti-ageing dimming green master batch for ginger greenhouse film and preparation method of special anti-ageing dimming green master batch
CN104558799A
High-tinting-strength flame-retardant general color master batch and preparation method thereof
CN112920490A